Direct growth of 2D and 3D graphene nano-structures over large glass substrates by tuning a sacrificial Cu-template layer. (5th May 2017) - Marchena, Miriam; Song, Zhen; Senaratne, Wageesha; Li, Connie; Liu, Xinyuan; Baker, David; Ferrer, Josep Canet; Mazumder, Prantik; Soni, Kamal; Lee, Robert; Pruneri, Valerio
Abstract: We demonstrate direct growth of two-dimensional (2D) and three-dimensional (3D) graphene structures on glass substrates. By starting from catalytic copper nanoparticles of different densities and using chemical vapour deposition (CVD) techniques, different 2D and 3D morphologies can be obtained, including graphene sponge-like, nano-ball and conformal graphene structures. More important, we show that the initial copper template can be completely removed via sublimation during CVD and, if need be, subsequent metal etching. This allows optical transmissions close to the bare substrate, which, combined with electrical conductivity make the proposed technique very attractive for creating graphene with high surface to volume ratio for a wide variety of applications, including antiglare display screens, solar cells, light-emitting diodes, gas and biological plasmonic sensors.